Wykuwanie prezydentury. Przyczyny i okoliczności decyzji o powołaniu urzędu Prezydenta PRL (1985–1988) - Pleskot, Patryk (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
W artykule podjęto próbę przeanalizowania przyczyn i okoliczności prowadzących do podjęcia przez Wojciecha Jaruzelskiego decyzji o powołaniu urzędu Prezydenta PRL. Proces ten nastąpił w drugiej połowie lat osiemdziesiątych i objął zarówno osobiście głównego decydenta w aparacie partyjno-państwowym schyłkowego PRL, lecz także jego najbliższe otoczenie oraz część establishmentu politycznego. Przyjrzano się nie tylko uwarunkowaniom wewnętrznym, lecz także międzynarodowym. Przeanalizowano koncepcje powołania urzędu prezydenckiego, z którymi zapoznawał się gen. Jaruzelski. Problematykę tę omówiono za pomocą analizy historycznej z uwzględnieniem podejścia charakterystycznego dla teorii procesu decyzyjnego oraz migration studies.

The article attempts to analize the causes and circumstances which led Wojciech Jaruzelski to make a decision to create the office of the President of People’s Republic of Poland. Such decision-making process took place in the second half of 1980’s. It was linked not only with gen. Jaruzelski (the main decision-maker in the late communist Poland) personally but also with his close subordinates and part of political establishment. The analysis deals with both inner determinants and the international ones. Some concepts of creating the presidential office have been described. The methodolical approach consists of historical analysis, decision-making theories and migration studies.
Forging the presidency. Causes and circumstances of the decision of creating the People’s Republic of Poland’s Presidential Office (1985–1988)
Keywords: prezydentura; PRL; Wojciech Jaruzelski; proces decyzyjny; presidency; People’s Republic of Poland; decision- making